Enhancing the feeding journey of the preterm infant in the NICU: the STAmmi VICINO pathway as a model of integrated and individualized neurodevelopmental care - Naboni, Cecilia; Costantino, Raissa Francesca; Longo, Stefania; Servi, Pierpaolo; Trussardi, Sonia; Tuoto, Maria Grazia; Ghirardello, Stefano; Orcesi, Simona (Frontiers in Public Health, 2025)
IntroductionPreterm birth remains a significant public health concern, with infants born before 32 weeks of postmenstrual age at a higher risk for various comorbidities and neurodevelopmental impairments. Feeding challenges are particularly prevalent in preterm infants due to the immaturity of their physiological functions. The neonatal intensive care unit (NICU) environment can exacerbate these vulnerabilities through unregulated sensory stimulation and limited parental contact.MethodsA multiprofessional focus group was conducted to identify roles and responsibilities among NICU healthcare providers to develop and implement an individualized, integrated, interprofessional, and multidimensional care protocol. The aim is to promote neurobehavioral and early feeding skills in preterm newborns in the NICU. The protocol was grounded in the Newborn Individualized Developmental Care and Assessment Program (NIDCAP) and European Standards of Care for Newborn Health, with a focus on minimizing stress, enhancing parental empowerment, and utilizing a cue-based feeding approach.ResultsThe resulting “STAmmi VICINO” pathway consists of six flexible joint meetings at the infant’s crib, involving parents and healthcare professionals, to provide comprehensive care strategies for the transition from enteral nutrition to autonomous sucking. Preliminary integration in the NICU practice demonstrated the feasibility and positive acceptance of the protocol among practitioners.DiscussionOral feeding skills in preterm infants should not be assessed separately from neurobehavioral development. An interdisciplinary, family centered approach is critical for successful early intervention programs that aim to positively impact neurodevelopment.